Blood sweep : a Posadas County mystery - Havill, Steven (Havill, Steven. Posadas County series, 2015)
Gifted fifteen-year-old Francisco Guzman has become an internationally renowned concert pianist, touring the world under the auspices of his music conservatory. That gives his mother, Posadas County Undersheriff Estelle Reyes-Guzman, plenty of reason to worry--and that's magnified when she learns that he's in Mexico's crime-ridden Mazatlan for a concert series where he may be the target for scam artists and kidnappers. Estelle's worries go from bad to worse when her uncle--a man she didn't know existed--surfaces in an attempt to mend family ties and leaves a trail of corpses in his wake. Estelle's attempts to glean family history--the story of her childhood in Tres Santos over the border--from her adopted mother, a woman now in her nineties, go nowhere. Meanwhile, escalating events put Sheriff Bobby Torrez in jeopardy, as they do newly wealthy rancher Miles Waddell and his pet project, the multi-million dollar theme park, NightZone, set high on a county mesa. Just when his sage advice might be most useful, former sheriff and family friend Bill Gastner takes a dive--in the shadows of his own garage. Now his far-flung family is added to the mix of people and events astir in the boot heel of New Mexico.